Gingival fibromatosis and significant tooth eruption delay in an 11-year-old male: a 30-month follow-up - K. KAVVADIA, E. PEPELASSI, C. ALEXANDRIDIS, A. ARKADOPOULOU, G. POLYZOIS, & K. TOSSIOS (Paediatric Dentistry, 2005)
This case report describes the dental management of an unusual case of idiopathic gingival fibromatosis with multiple impacted primary teeth, and the absence of eruption of permanent teeth, in an 11-year-old boy and at the 30-month follow-up.